Brown bears in Alaska's national parks: conservation of a wilderness icon - Hilderbrand, Grant V., editor; Joly, Kyle, editor; Gustine, David D., editor; Chambers, Nina, editor; University of Alaska Press, publisher (Colorado State University. Libraries, 2025)
Explores the conservation, ecology, and management of brown bears in Alaska's national parks. Written by wildlife biologists, it examines bear biology, climate change impacts, and human-bear interactions in diverse ecosystems. For conservationists and nature enthusiasts.--Provided by publisher.
Stewardship: Preserving Bears for Future Generations / Grant V. Hilderbrand, Andee Sears, David Payer, and Nina Chambers -- Bears and Humans: An Ancient Relationship That Persists Today / Rachel Mason, Amy Craver, Dael Devenport, Karen Evanoff, Victoria Florey, Mary Beth Moss, Marcy Okada, Jack Omelak, and Dillon Patterson -- Ecology: How Bears Live in Their World / Grant V. Hilderbrand, Kyle Joly, William Deacy, and David D. Gustine -- Human-Bear Interactions: The Challenge of Coexistence / Lindsey Mangipane, Kelsey Griffin, Kyle Joly, Tania Lewis, Buck Mangipane, Patricia Owen, Andee Sears, and Grant V. Hilderbrand -- Climate Change: Can Bears Adapt to a Dynamic World? / William Deacy, Kyle Joly, Nina Chambers, David D. Gustine, Grant V. Hilderbrand, Kim A. Jochum, Pam Sousanes, and David K. Swanson -- Population Estimation: How Many Bears Are There? / Joshua H. Schmidt -- Glacier Bay: Bears in the Bay That Glaciers Built / Tania Lewis and Mary Beth Moss -- Denali: From Murie to Modern Day / Patricia Owen -- Gates of the Arctic: Bears in the Brooks Range / Kyle Joly, Mathew S. Sorum, Matthew D. Cameron, William Deacy, Grant V. Hilderbrand, Susan Georgette, and David D. Gustine -- Katmai: The Greatest Concentration of Bears on the Planet / Kelsey Griffin, Michael Saxton, Joy Erlenbach, Leslie Skora, Troy Hamon, Laura Stelson, and Grant V. Hilderbrand -- Lake Clark: Diverse Life Histories amid Myriad Pressures / Buck Mangipane, Lindsey Mangipane, Karen Evanoff, and John Branson -- Ecological Variation: Resilience in Times of Change / Grant V. Hilderbrand, Diana Lafferty, and Lindsey Mangipane -- Conclusion: The Future of Brown Bear Conservation, Management, and Science in Alaska's Parklands / Kyle Joly, David D. Gustine, Nina Chambers, and Grant V. Hilderbrand.
Keywords: Kodiak bear -- Alaska -- History; Brown bear -- Alaska -- History; National parks and reserves -- Alaska -- History; Wildlife management -- Alaska; National parks and reserves -- Management -- History